2020
DOI: 10.3390/cells9102200
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Podoplanin, CD44s and CD44v in Squamous Carcinoma Cells

Abstract: Podoplanin and CD44 are transmembrane glycoproteins involved in inflammation and cancer. In this paper, we report that podoplanin is coordinately expressed with the CD44 standard (CD44s) and variant (CD44v) isoforms in vivo—in hyperplastic skin after a pro-inflammatory stimulus with 12-O-tetradecanoylphorbol-13-acetate (TPA)—and in vitro—in cell lines representative of different stages of mouse-skin chemical carcinogenesis, as well as in human squamous carcinoma cell (SCC) lines. Moreover, we identify CD44v10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 79 publications
(133 reference statements)
0
18
0
Order By: Relevance
“…Since podoplanin is induced to cluster in cholesterol-rich regions upon CLEC-2 binding (2), we hypothesised that membrane partner proteins of podoplanin may also be required to downregulate podoplanin-driven contractility for FRC network elongation. A known partner protein of podoplanin, the hyaluronic acid receptor CD44 (19, 20), is also specifically upregulated on TRCs, but not on MRCs or LECs (Fig. 1e-g).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since podoplanin is induced to cluster in cholesterol-rich regions upon CLEC-2 binding (2), we hypothesised that membrane partner proteins of podoplanin may also be required to downregulate podoplanin-driven contractility for FRC network elongation. A known partner protein of podoplanin, the hyaluronic acid receptor CD44 (19, 20), is also specifically upregulated on TRCs, but not on MRCs or LECs (Fig. 1e-g).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that podoplanin and CD44 can directly interact via either their extracellular domains (19), or their transmembrane and cytoplasmic domains (20). Podoplanin and CD9 are also confirmed as direct partner proteins, interacting through the transmembrane domain of podoplanin and CD9 transmembrane domains 1 and 2 (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a Phase I clinical trial with Maackia amurensis seed lectin (MASL), which can target podoplanin, is set to start for the treatment of squamous cell carcinoma of head and neck (NCT04188665) (163,164). Podoplanin is a mucin like sialoglycoprotein, co-expressed with CSC marker CD44 and CD44v (165). However, lectins may also bind to healthy cells presenting SA.…”
Section: Targeting Altered Glycosylation In Cancer Cells and Cscsmentioning
confidence: 99%